In the Zoom Where It Happened: Telepractice and the Voice Clinic in 2020 - Becker, Diana Rose; Gillespie, Amanda I. (Seminars in Speech and Language, 2021)
Telemedicine—conveying medical information virtually for planning, diagnosis, or treatment—has been a part of the American medical system for over 100 years. A constantly evolving modality, telepractice was a supplemental care delivery system for most speech-language pathologists (SLPs) until March 2020 when the COVID-19 pandemic forced clinical operations to halt in-person activities and convert as much as possible to virtual platforms. The purpose of this article is to provide an overview of the need for telepractice prior to and beyond the current pandemic, the efficacy of telepractice for the voice-specialized SLP, limitations of telepractice, and best practices for providing care over telepractice with a specific focus on voice disorder diagnosis and treatment.
Keywords: telemedicine; telepractice; voice; speech-language pathology; voice disorders